ATTİLÂ İLHAN ŞİİRİNDE GÖRSELLİK VE SİNEMATOGRAFİ - (:unkn) unknown (My University, 2017)
Attilâ İlhan, 1940 Kuşağı içinde kendine özgü yeri olan bir şairdir. Sinemayı genç yaşlarından itibaren çok seven Attilâ İlhan'ın poetikası büyük ölçüde sinema yapısı üzerine temellenir. Genç yaşta Paris ve İstanbul'da sürekli olarak sinema salonlarında bulunmuş, film eleştirileri yazmıştır. Şiir yazarken de imgelerini genellikle sinematografik çağrışımlardan seçmiştir. Sinematografide genel olarak görüntü, hareket, ses-görüntü eşzamanlılığı önemlidir ve Attilâ İlhan'ın şiir anlayışı büyük ölçüde sinema tekniğine ve görsel imgelere dayanır. Şiirinin imgeleri sinema perdesine yansıyan görüntüler gibidir. O, Şiirsel Gerçekçi Fransız Sinemasından yararlanmış ve şiirlerini bu anlayışla yapılandırmıştır. Attilâ İlhan, imge oluştururken öykülemeci ve/veya betimlemeci teknik, fotoğraflama tekniği, çağrışım kurgusu, çarpıcı kurgu gibi tekniklerden yararlanır. Şiirlerinde adeta bir sinema dekoru yaratır, sinema diline yakın duran tekniğiyle benzersiz bir poetikaya ulaşır.

Attilâ Ilhan is a poet who has a unique place in the 1940s generation. Attila Ilhan's poetry, who loves cinema from its young age, is based on cinema structure to a great extent. At a young age he was constantly in cinema halls in Paris and Istanbul and he wrote film critiques. When writing poetry, he often chose his images usually from cinematographic associations. In cinematography, visual, motion, audio-visual synchronicity is important in general, and Attila Ilhan's understanding of poetry is largely based on cinematography and visual imagery. The images of poetry are like the images reflected in the cinema scene. He benefited from the Poetic Realist French Cinema and structured his poetry with this understanding. When Attilâ Ilhan creates the image, narrator and / or descriptor uses techniques such as technique, photography technique, associative editing, striking editing. He creates a cinema decor in his poems and reaches a unique poetic with his technique that is close to the language of cinema
VISUALITY AND CINEMATOGRAPHY IN ATTILA ILHAN POETRY
Keywords: Film, Radyo, Televizyon